The use of 18S rRNA for identification of the first record of Tadpole Shrimp Lepidurus apus (Linnaeus, 1758) from Jordan - SAQR ABUSHATTAL; HUSSEIN ALNASARAT; SULAIMAN M. ALNAIMAT; EHAB EID (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Abushattal S, Alnasarat H, Alnaimat SM, Eid E. 2024. The use of 18S rRNA for identification of the first record of Tadpole Shrimp Lepidurus apus (Linnaeus, 1758) from Jordan. Biodiversitas 25: 1223-1229. The tadpole shrimps are living fossils that survive in temporary water pools and are considered benthic organisms that swim and feed on tiny organisms. Two genera of tadpole shrimps exist worldwide: Triops and Lepidurus, which share similar ecological niches and habitats but never coincide. The occurrence of the tadpole shrimp Lepidurus apus in Jordan was confirmed for the first time using the 18S rRNA Gene-Based PCR Assay. The experimental approach encompassed the amplification of biological specimens utilizing a universal amplicon measuring approximately 1,500 base pairs (bp), specifically targeting the 18S ribosomal RNA (rRNA) gene. Subsequently, the acquired sequences underwent scrutiny through BlastN search against the GenBank database for validation and comparative analysis. Genetic analysis was needed to define the species accurately, especially with tadpole shrimp's generally high morphological variability. This species was recorded in a temporary freshwater pool in the desert of Al-Jafr in Ma’an governorate in southern Jordan. The DNA analysis showed a 100% identical sequence of the 18S rRNA gene with Lepidurus apus sequences. This record is important due to the ecological role of the tadpole shrimps as filter feeders, consuming algae, bacteria, and other small particles of organic matter, and as a food source for various fish, birds, and other aquatic animals. In addition, it will pave the way for future research to identify its economic importance, such as its role in mosquito control and its potential role in aquaculture. Finally, tadpole shrimp are sensitive to environmental changes and could be used to indicate climatic changes and habitat degradation. This is mainly due to their sensitivity to changes in water quality, including temperature, pH, and chemical composition, and their niche requirements for survival and reproduction. In addition, monitoring tadpole shrimp distribution and comparing it with historical records can reveal patterns of climate-induced range shifts.